2006
DOI: 10.2164/jandrol.05187
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Sperm‐Preserving Proteins in the Ram Reproductive Tract

Abstract: Previously, we reported that the addition of seminal plasma proteins before cold-shock treatment prevents sperm membrane injury, and that 2 proteins of approximately 14 (P14) and 20 (P20) kDa, the main components of fraction 6 isolated by exclusion chromatography, are responsible for this protective effect. The objective of the present study was to localize P14 and P20 in tissues of the ram reproductive tract to determine their origin. Antiserum generated against purified P14 and P20 reacted with proteins in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
2
14
0
3
Order By: Relevance
“…Our data are consistent with those in a previous report in which we identified the presence of a seminal plasma protein in the ram sperm membrane (RSVP14, Fernandez-Juan et al 2006), phosphorylated at serine and threonine residues, which undergoes a partial loss and redistribution during capacitation and acrosome reaction towards the post-acrosomal and equatorial regions (Barrios et al 2005). The results of the present study support our previous suggestion that serine/ threonine phosphorylation may play an important role in sperm capacitation, since consolidation of phosphoproteins to specific domains of the head and tail may facilitate the acrosome reaction and egg penetration (Naz 1999).…”
Section: Localization Of Phosphoproteins In Ram Spermsupporting
confidence: 93%
“…Our data are consistent with those in a previous report in which we identified the presence of a seminal plasma protein in the ram sperm membrane (RSVP14, Fernandez-Juan et al 2006), phosphorylated at serine and threonine residues, which undergoes a partial loss and redistribution during capacitation and acrosome reaction towards the post-acrosomal and equatorial regions (Barrios et al 2005). The results of the present study support our previous suggestion that serine/ threonine phosphorylation may play an important role in sperm capacitation, since consolidation of phosphoproteins to specific domains of the head and tail may facilitate the acrosome reaction and egg penetration (Naz 1999).…”
Section: Localization Of Phosphoproteins In Ram Spermsupporting
confidence: 93%
“…The complex mixture of a wide variety of components in seminal plasma affects the survival of sperm. Certain seminal plasma protein bands have been identified in boar semen that could prevent cold shock injury [19]. In the present study, individual responses to the presence and absence of seminal plasma were observed after cold shock, and semen volumes and sperm concentrations varied among the five rhesus macaque males, which indicated that the components of seminal plasma and the proteins that could prevent cold shock might be genetically inherited rather than being random.…”
mentioning
confidence: 47%
“…We have already shown that RSVP14 and RSVP20 (ram seminal plasma proteins) are adsorbed onto the ejaculated ram sperm surface [75], and that they are redistributed and partially lost from the plasma membrane during in vitro capacitation and the acrosome reaction (only approximately 35% of them remained on the spermatozoa after both processes, [76]. Thus, we can speculate that there is both a loss and a redistribution of proteins in discrete plasma membrane domains.…”
Section: Discussionmentioning
confidence: 96%